Earth's distant magnetotail current sheet near and beyond lunar orbit. Issue 10 (26th October 2015) - Vasko, I. Y.; Petrukovich, A. A.; Artemyev, A. V.; Nakamura, R.; Zelenyi, L. M.
Abstract: We analyze the structure of the Earth magnetotail current sheet (CS) in middle, X ∈[−50, −20] R E, and distant, X ∈[−100, −80] R E, regions using data set of 573 CS crossings by Geotail in 1994–1995. For a subset of 213 CSs we determine the CS thickness L, average current density j 0, and velocity v D = j 0 / e n 0 ( n 0 is the ion number density). We find similar dawn‐dusk distributions of CS parameters for middle and distant tail: L is about 3000 km at the dusk flank and grows up to 12, 000 km toward the dawn flank; j 0 grows toward the dusk flank by a factor of 2–3; and the most intense CSs (with higher v D ) are observed near midnight. We show that ion‐scale CSs with the thickness of several ion thermal gyroradii (say less than seven) are observed in middle and distant tail in more than 50% of crossings. For observed CSs electrons likely provide the dominant contribution to the current density. We divide the subset into intense and weak CSs (using parameter v D ). Weak CSs have thickness of about 20 ion thermal gyroradii and B z of about 1.5 nT. Intense CSs have thickness of about 3–7 thermal gyroradii and much smaller B z implying more stretched field line configuration. Intense CSs are accompanied by fast ion flows: v D is larger for larger amplitudes of ion bulk velocity v x that is likely due to larger contribution of Speiser ions. The properties of the CS in middle and distant tail are compared with those found for the near‐Earth tail. Key Points: We collected data set of current sheets near and beyond the lunar orbit with determined thickness Ion‐scale current sheets are frequently observed near and beyond the lunar orbit The most intense current sheets are observed in the presence of fast earthward/tailward plasma flows